Preparation and structural elucidation of 2-Acetoxy-methyl-5-tert.-butyl furan from sucrose - Lim, Remedios Abella
A non-food product from sucrose, 2-acetoxy-methyl-5-tertiary-butyl furan has been prepared through a series of reactions. The course of the chemical reactions involved is characterized through the intermediates. Classical tests, NMR spectroscopy and IR spectroscopy furnished compelling evidences for the following intermediates and final product in the reaction series: 1) 5-methyl-2-furfuryl alcohol 2) 2-acetoxy-methyl-5-methyl furan 3) 5-acetoxy-methyl-2-furoic acid 4) 2-acetoxy-methyl furan 5)2-acetoxymethyl-5-tert.-butyl furan. The first stage of synthesis which involved essentally the preparative method of Rinkes, led to the formation of 5-methyl-2-furfuryl alcohol. Detailed structural characterization of the final product is discussed and detailed mechanistic steps are proposed for the conversion of sucrose to 2-acetoxy-methyl-5-tert.-butyl furan.